METHODS OF STRENGTHENING AND PROTECTION OF UNDERGROUND CAPITAL DEPOSITS - Nomdorov , Rustam Uralovich; Khasanov , Shahzod Rasul ugli (Digital technologies in industry, 2025)
This article provides detailed information about the methods of strengthening and protection of underground mine workings. When designing capital workings, it is important to select the necessary methods of protection of the seams in areas outside the influence of mining operations. The article provides instructions on the use of various methods of reinforcement, including compensatory recesses and anchor fastening, taking into account the technological and geological characteristics of underground mine workings. Methods for calculating the average compressive strength of workings, equivalent power, and “shift-under” convergence are also described. When strengthening and protecting capital workings, their geological conditions, compressive strength of the formations, and service life are taken into account. The article proposes the necessary methodology for ensuring mine protection and stability.